Non-application of the nursing process at a hospital in Accra, Ghana: lessons from descriptive research - Agyeman-Yeboah, J.; Korsah, K.A. (BMC Nursing, 2018)
Background Registered nurses in Ghana are trained to plan the care that they provide to their patients in a systematic and organized manner. This scientific approach to care is known as the nursing process. There is evidence that the nursing process is not being practised by professional nurses in Ghana, as expected. This research seeks to explore what informs nursing interventions in the clinical area. Methods A qualitative study was conducted with ten registered nurses; and this was descriptive in nature. One-on-one interviews were conducted with the research participants, as a means of collecting the data. A semi-structured interview guide was used as the data-collecting tool. The collected data were analysed by using latent-content analysis. Three main themes emerged from the data analysis. Results It was found that registered nurses did not plan their nursing care. The care that the nurses provided was based on routine nursing care and doctors’ orders, both verbal and non-verbal; or written communication were the means whereby the care was provided; and that was communicated among the nurses. Conclusion Registered nurses are taught the nursing process; and they are expected to implement the acquired knowledge in the clinical area. The failure of nurses to practise the expected standard of care results in their relying on the decision of other health-care professionals, such as doctors. This makes registered nurses appear to be assistants to doctors. We, therefore, conclude that nurse leaders must supervise nurses to put into practice what they were taught during their training; so that they can have professional autonomy in their practice as nurses. It is also suggested that nurses must show evidence of using the nursing process in their daily work by the use of the nursing care-plan form.
Keywords: Nursing process; Nursing care-plan; Non-usage; Nurses